The phantom tollbooth - Juster, Norton, 1929-; Feiffer, Jules (New York : Random House, 1961)
Milo travels through a magical tollbooth and begins a journey to the Kingdom of Wisdom, where he and a "watch" dog named Tock try to end the feud between numbers and words.
Book Links (A.L.A.)
Elem. School Library Collection
Wilson's Children
5.4
5-8
5-8
Keywords: Fantasy; Fantastic fiction